KAJIAN BIODIVERSITAS BIOTA LAUT (EKHINODERMATA, MOLUSKA) DI PERAIRAN PULAU PARI, PULAU SERIBU - Sunarto (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2014)
Coastal ecosystems is one of the shallow marine ecosystems are productive, but it is unfortunate that this ecosystem research in Indonesian waters are rare. Where matters relating to the biology and ecology of marine biota (molluscs and ekhinoderms) in the coastal tropical region has not been revealed, including in coastal areas of Pari Island and its surrounding waters. Coastal ecosystem here have the potential of natural resources is very important for the life of the Indonesian nation, which is one member of the United Nations Convention on biodiversity and one of seven countries that have a